Pengaruh Keaktifan Mahasiswa dalam Berorganisasi terhadap Kesiapan Kerja Mahasiswa Departemen Teknik Mesin FT UNP (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
The importance of education in improving the standard of living of mankind, especially in facing the challenges of globalization and labor market competition. The purpose of this study is to determine how organizational involvement in students affects the work readiness of students in the Department of Mechanical Engineering, Faculty of Engineering, Padang State University. Using a quantitative strategy with correlational techniques, data collected through questionnaires from 49 proportionally selected students. The results of the analysis show that there is a positive and substantial influence between organizational involvement on work readiness as reflected through the regression coefficient value which reaches 0.883 and R Square of 0.781. This indicates that involvement in organizations explains 78.1% of the work readiness variable. This finding highlights the importance of student involvement in organizational activities as an effort to improve readiness to face the world of work.